PENGARUH FOTOPERIODE TERHADAP AKTIFITAS PERTUMBUHAN DAN KELANGSUNGAN HIDUP IKAN PATIN SIAM (Pangasius hypophthalmus) - Muhammad Yuda Setiawan; M. Adriani; Akhmad Murjani (Fish Scientiae, 2019)
The purpose of this study was to determine the effect of photoperiod on the growth and survival of siamese catfish (Pangasius hypopthalmus). The results of the research data showed the highest growth rate relative weight in the treatment of A (0 T: 24 G) to the average value -value 1713.3, The highest growth rate relative to the length of treatment A (0 T: 24 G) to the average value -rata 145.7, The highest daily growth rate in the treatment of A (0 T: 24 G) to the average value - value 5.17, and the highest survival in the treatment of A (0 T: 24 G) with a mean value of89.3 value. The statistic shows that there are very real differences between the treatment given, and test results further stated that treatment A highly significant compared with other treatments.Then the calculation results continued to be a factor supporting parameter condition, also obtained the highest score in the treatment of A (0 T: 24 G) to the average value – value 0.82 and the highest feed efficiency in treatment A (0 T: 24 G) with a mean value - value 159.6 and waterquality data that is still in the range and standard of living desired. Data growth and survival showed that the longer the dark period is given, the better the growth and survival, because the dark atmosphere to give effect to test the appetite of fish, according to his habits are active at night (nocturnal). Means the results of this study to answer the hypothesis, H1 accept and reject Ho where foto periode given effect on the growth and survival of the test fish.